Ask me: Children's experiences of pain explored using the draw, write, and tell method - Pope, Nicole; Tallon, Mary; Leslie, Gavin; Wilson, Sally (Wiley-Blackwell Publishing, Inc., 2018)
© 2018 Wiley Periodicals, Inc. Purpose: Pain management within emergency departments (ED) remains challenging. Given that unrelieved pain in children is linked to a number of negative physiological and psychological consequences, optimal management of children's pain is paramount. Many studies exploring children's pain have adopted quantitative methods or sought the perspectives of adults. Compared to adults, studies examining children's views on pain and pain management are limited. This study aimed to explore children's pain experiences, their perception of pain management and expectations of the role of the nurse. Design: This was a qualitative descriptive study using an inductive approach. Methods: Fifteen children, aged 4-8 years who presented to the ED of an Australian tertiary pediatric hospital in acute pain participated. Data were collected using draw, write, and tell (DWT) technique and analyzed using thematic analysis. Results: Three themes emerged (1) "Security," (2) "My pain" with subthemes: "The pain feelings" and "My sad/happy feelings," (3) "Comfort and relief" with subthemes: "Taking my mind off it," "Resting" and "Hospital things." When in pain children needed to feel secure. Parents and nurses were important in fostering a secure environment for children. Children were capable of describing their pain and identified nonpharmacological strategies to help their pain. Practice implications: Children as young as 4 years old can provide detailed accounts of their pain, which extends beyond physical dimensions to include visual, auditory, and sensory features. Nurses need to listen, be honest, and develop trust with children to be helpful. Nonpharmacological pain-relieving strategies can be implemented by parents and nurses in collaboration with the child. Fostering a secure environment is essential.